Mary Poppins [videorecording (DVD)] - Andrews, Julie; Van Dyke, Dick; Tomlinson, David, 1917-2000; Johns, Glynis; Dotrice, Karen; Garber, Matthew; Wynn, Ed, 1886-1966; Travers, P. L. (Pamela Lyndon), 1899-1996 ([publisher not identified], 2013)
A beloved classic shines like never before with an all-new digital restoration. Winner of five Academy Awards, including best actress (Julie Andrews), best song (Chim Chim Cher-ee), and best visual effects. Mary Poppins flies out of the windy London skies and into the home of two mischievous children. With the help of a carefree chimney sweep named Bert (Dick Van Dyke), the spirited nanny turns every chore into a game, and every day into a 'Jolly Holiday.'